Biological Therapy for Asthma - Resti Yudhawati; Megawati Rif’atyyah Nozomi Guntur (Jurnal Respirasi, 2021)
Asthma is a heterogeneous chronic inflammatory disease in the respiratory tract that leads to recurrent episodic symptoms. Study about the mechanism of pathophysiology and immunology which stimulates chronic inflammation in asthma has been greatly developed. The understanding of inflammation mediator that is predominant on various asthma phenotypes could be useful for development of diagnosis and targeted therapy. Standard asthma therapy administered through the airway has limited effects only in the airway. The knowledge of molecular pathophysiology and immunology of this disease developed interest of the drugs that perform proximally from inflammation process in the airway, in this case is biological therapy. Several biological therapies have been investigated for its efficacy on human, including Anti IgE (Omalizumab), Anti Interleukin-5 (Mepolizumab, Reslizumab, Benralizumab), Anti Interleukin-4/Interleukin-13 (Dupilumab), and Anti Interleukin-17 (Secukinumab and Brodalumab).